Akuntabilitas dan Transparansi Pengelolaan Penyaluran Bantuan Langsung Tunai Dana Desa - Rizky Arief Fadhilla; Kamilah; Mawaddah Irham (AKUA: Jurnal Akuntansi dan Keuangan, 2024)
This research aims to determine accountability and transparency in the management of the distribution of Direct Village Fund Cash Assistance (BLTDD) in Jaring Halus Village, Secanggang District, Langkat Regency. The approach method in this research is a descriptive qualitative method. The data collection techniques used were observation and interviews conducted directly in the field as well as documentation to support this research. Based on the results obtained, the implementation of accountability in BLTDD management is said to be quite good, in planning the allocation of village funds, responsibility in managing village funds and realizing part of the development planning in Jaring Halus Village. Apart from that, the village government still has shortcomings, such as only involving the community during the planning stage, while at the next stage only the village government knows and also all plans discussed by village officials are not all realized. Apart from that, in implementing transparency in BLTDD management, the village government does not apply transparent principles in managing village funds. This is due to the lack of openness to the community in managing village fund allocations in village development, and there are still many limitations to the community in obtaining information regarding the management of village fund allocations.